A STUDY OF EYE CONDITIONS RELATED TO RETINAL VEIN OCCLUSION - Manish Totey (Journal of Biomedical and Pharmaceutical Research, 2018)
BACKGROUND: A significant factor in vision loss is retinal vein occlusion (RVO). Branch retinal vein occlusion (BRVO) is 4–6 times more common than central retinal vein occlusion (CRVO) among the two primary kinds of RVO. Ageing is a primary risk factor for RVO. Systemic diseases include hypertension, arteriosclerosis, diabetes mellitus, hyperlipidemia, vascular cerebral stroke, blood hyperviscosity, and thrombophilia are additional risk factors. Metabolic syndrome (hypertension, diabetes, and hyperlipidemia) is a significant risk factor for RVO. RVO risk is significantly higher in people with end-organ damage brought on by diabetes mellitus and hypertension. Additionally, socioeconomic status appears to be a risk factor. Compared to non-Hispanic whites, American blacks are diagnosed with RVO more frequently. Some research indicate that women are less at risk than men. It is still debatable how thrombophilic risk factors affect RVO. AIM: The study’s goal is to investigate the ocular morbidities brought on by retinal vein blockage. MATERIAL AND METHOD: This cross-sectional observational study was conducted in the department of ophthalmology. Prior to the assessment, all subjects provided their written, informed consent. They were informed of and given an explanation of the study’s purpose. The patient’s name, age, and gender were documented. The questioner inquired about the illness’s past. The question of any prior ocular trauma was raised. It was asked if there had ever been any eye surgeries. A systemic illness history was gathered. A comprehensive ophthalmologic examination was performed on all individuals. A Snellen’s Chart that was lit was used to evaluate the vision. There was a thorough slit lamp assessment. A direct ophthalmoscope, an indirect ophthalmoscope, and slit lamp biomicroscopy were used for dilated fundoscopy. When necessary, an optical coherence test was performed to confirm the existence of macular edema. Acuity between 6/18 to 6/60 was considered to be visual impairment, whereas acuity greater than 6/18 was considered to be blindness. RESULTS: The patients ranged in age from 41 to 77, with a median age of 66 and a mean age of 58. There were 57 female patients and 43 male ones. 54 patients had BRVO, 38 patients had CRVO, and 8 individuals had HRVO. Statistics did not support the relationship between BCVA and RVO. 11 BRVO patients also experienced macular edema. Vitreous hemorrhage (VH) was present in 16 individuals with CRVO, while ME and iris neovascularization (INV) were present in 9 and 3 patients, respectively. Disc neovascularization (DNV) affected 4 patients. One HRVO patient had VH. Compared to patients with BRVO and HRVO, patients with CRVO had a higher incidence of ocular problems. CONCLUSION: Complications that could endanger vision have been observed with RVOs. Therefore, it is crucial to diagnose the disease as soon as possible. The burden of blindness can then be considerably reduced by using a variety of treatment approaches to address these issues. In our hospital, central retinal vein occlusion is more typical compared to peripheral retinal vein occlusion. Women are more likely than men to be impacted. RVO-related problems can cause blindness that is irreversible. Early diagnosis of these can therefore contribute to lowering the social cost of blindness. KEYWORDS: Retinal vein occlusion, Branch retinal vein occlusion, Central retinal vein occlusion, Incidence, Pattern, Risk Factors.